THE EXISTENCE OF FINE PAYMENT AS AN ALTERNATIVE PUNISHMENT IN COURT - Zainal Abidin Pakpahan (Jurist Argumentum: Pemikiran Intelektual Hukum, 2023)
The existence of fines as one of the main types of punishment contained in Indonesian criminal law, has been a form of punishment applied since the time of the Dutch Criminal Code until now it has been adopted by Indonesia as its colonial country. The enactment of Law Number 1 of 1946 concerning Criminal Law Regulations which is a transplant of the Dutch Criminal Code into national criminal law, until the birth of a new Criminal Code based on Law Number 1 of 2023 concerning the Criminal Code, the existence of fines as a form of principal crime, is maintained so that the scope of the new criminal fines regulation. The new Criminal Code continues to categorize fines as one of the main types of criminal penalties, both in the new Criminal Code and the Old Criminal Code, such as, classification of criminal fines into eight categories, time period and method of payment of criminal fines, provisions regarding confiscating and auctioning off the property/belongings of convicts who do not pay fines, substitute penalties for fines which were previously in the form of imprisonment into prison sentences, supervision penalties and social work penalties which are the regulations governing the new Criminal Code